Has the COVID-19 delayed the diagnosis of fetal anomalies and reduced in the follow-up of high-risk pregnancies? - Eda Özden Tokalıoğlu; Şule Göncü Ayhan; Fatma Didem Yücel Yetişkin; Deniz Oluklu; Berchan Besimoğlu; Esin Merve Erol Koç; Betül Yakıştıran; Atakan Tanaçan; Elif Gül Eyi; Özlem Moraloğlu Tekin; Dilek Şahin (Perinatal Medicine Foundation, 2022)
Objective: COVID-19 has deeply affected our lives in terms of social, economic, education and health issues. Pregnant women have had concerns about routine antenatal care visits and decreased follow-up numbers due to concern of COVID-19 transmission. We aimed to evaluate whether there is a delay in the diagnosis of fetal anomaly during the COVID-19 pandemic period and whether patients diagnosed with fetal anomaly attend antenatal care regularly or not, and to investigate the factors that prevent them from regular follow-up. Methods: Pregnant women diagnosed with fetal anomaly during pandemic period (March 1, 2020 to September 1, 2020) and diagnosed with fetal anomaly before pandemic period (September 1, 2019 to February 28, 2020) were compared with a questionnaire in terms of antenatal follow-up frequency and gestational age of fetal anomaly diagnosis. Results: In the during pandemic period group, regular pregnancy follow-up was decreased from 87% to 51% because of maternal anxiety, fear of virus transmission in hospital and the anxiety of passing it on to baby. Attending a detailed ultrasound scan for detecting fetal anomaly at 18-22 weeks was significantly lower in the during pandemic group. In the pandemic period, the most commonly diagnosed fetal anomalies were central and peripheral nervous system, and cardiovascular and gastrointestinal system anomalies similar to the before pandemic period group. The mean frequency of follow-ups in the third trimester in the before pandemic period group and during pandemic period group was 6.02 (±2.36) times and 4.02 (±1.97) times, respectively, and it was a considerable and statistically significant decrease. In addition, the mean week of fetal anomaly diagnosis was 23±6 weeks in during pandemic group, while it was 22±5 weeks in before pandemic group, and there was no statistically significant difference. Conclusion: Antenatal follow-up of the patients has been decreased significantly during the pandemic period, although it does not seem to cause delay in the diagnosis of fetal anomaly. In experienced perinatal centers, if the concerns of patients are relieved and they are examined under suitable conditions for the pandemic, there will be no delay in diagnosis of fetal anomalies.